Biotransformations Utilizing β-Oxidation Cycle Reactions in the Synthesis of Natural Compounds and Medicines - Œwizdor, Alina (Molecular Diversity Preservation International (MDPI), 2012)
β-Oxidation cycle reactions, which are key stages in the metabolism of fatty acids in eucaryotic cells and in processes with a significant role in the degradation of acids used by microbes as a carbon source, have also found application in biotransformations. One of the major advantages of biotransformations based on the β-oxidation cycle is the possibility to transform a substrate in a series of reactions catalyzed by a number of enzymes. It allows the use of sterols as a substrate base in the production of natural steroid compounds and their analogues. This route also leads to biologically active compounds of therapeutic significance. Transformations of natural substrates via β-oxidation are the core part of the synthetic routes of natural flavors used as food additives. Stereoselectivity of the enzymes catalyzing the stages of dehydrogenation and addition of a water molecule to the double bond also finds application in the synthesis of chiral biologically active compounds, including medicines. Recent advances in genetic, metabolic engineering, methods for the enhancement of bioprocess productivity and the selectivity of target reactions are also described.